2019
DOI: 10.3390/molecules24193557
|View full text |Cite
|
Sign up to set email alerts
|

Photostabilization of Poly(vinyl chloride) by Organotin(IV) Compounds against Photodegradation

Abstract: Poly(vinyl chloride) (PVC), a polymer widely used in common household and industrial materials, undergoes photodegradation upon ultraviolet irradiation, leading to undesirable physicochemical properties and a reduced lifetime. In this study, four telmisartan organotin(IV) compounds were tested as photostabilizers against photodegradation. PVC films (40-µm thickness) containing these compounds (0.5 wt%) were irradiated with ultraviolet light at room temperature for up to 300 h. Changes in various polymeric para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 50 publications
0
42
1
Order By: Relevance
“…Complex 1, which is highly aromatic (three phenyl, two aryl, and one tetrazole moieties) was the most efficient additive for stabilizing the polymeric materials. It has been reported that additives containing aromatic moieties are more efficient PVC photostabilizers compared with the corresponding ones containing aliphatic residues [31]. Complex 1 absorbs UV irradiation directly and releases the adsorbed energy over a long period of time at a rate that is not harmful to the PVC chains.…”
Section: Assessment Of Photodegradation Of Pvc Using Energy Dispersivmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex 1, which is highly aromatic (three phenyl, two aryl, and one tetrazole moieties) was the most efficient additive for stabilizing the polymeric materials. It has been reported that additives containing aromatic moieties are more efficient PVC photostabilizers compared with the corresponding ones containing aliphatic residues [31]. Complex 1 absorbs UV irradiation directly and releases the adsorbed energy over a long period of time at a rate that is not harmful to the PVC chains.…”
Section: Assessment Of Photodegradation Of Pvc Using Energy Dispersivmentioning
confidence: 99%
“…The substituents on the synthesized tin complexes are varied to include aliphatic (butyl groups) or aromatic substituents (phenyl groups). Recently, various additives (Figure 1), including polyphosphates [18][19][20], Schiff bases [21][22][23][24][25], aromatic compounds [26,27], and organic-metal complexes [28][29][30][31], were investigated for use as PVC stabilizers. Some success has been achieved; however, research into the design of new and efficient PVC stabilizers for use on the commercial scale is ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…The main use of organotin (IV) compounds is to stabilize PVC against UV light [11]. Several di-organotin (IV) and tri-organotin complexes were syntheses by the reaction of Ph 3 SnCl, Ph 2 SnCl 2 , Bu 3 SnCl, Me 3 SnCl and Me 2 SnCl 2 with different ligands such as benzamidoleucine [12], ciprofloxacin [13,14], benzamidoacetic acid [15], benzamidoglycin [16], furosemide [17], naproxen [32] and telmisartan [33].…”
Section: Organotin(iv) Complexesmentioning
confidence: 99%
“…Emad's group used Polyphosphates as photostabilizers of PVC [13]. Figure 1) were synthesized from the reaction of telmisartan and the appropriate tin(IV) chloride salts as previous reported [16]. The complexes have been characterized by FTIR, 1 H-, 13 C-and 119 Sn-NMR spectroscopies, elemental analysis and Field Emission Scanning Electron Microscopy (FESEM), as reported [16].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1) were synthesized from the reaction of telmisartan and the appropriate tin(IV) chloride salts as previous reported [16]. The complexes have been characterized by FTIR, 1 H-, 13 C-and 119 Sn-NMR spectroscopies, elemental analysis and Field Emission Scanning Electron Microscopy (FESEM), as reported [16]. The preparation of polymeric Films 5 g of PVC was dissolved in 100 mL of THF and left to stir for 30 min at 25 C, after that 0.5 wt% of the new stabilizers (1, 2, 3, or 4) was added to the mixture and left to stir for more 30 min.…”
Section: Introductionmentioning
confidence: 99%